SMART MONITORING AND WATERING OF CHILI PLANTS USING A FUZZY MAMDANI SYSTEM - Reza Syafrian Setiadi; Feri Sulianta (Informatika, Universitas Jenderal Soedirman, 2023)
In this research, the design and manufacture of a prototype for a monitoring and watering system that integrates the concept of fuzzy logic in chili plants are carried out. The relationship between air humidity, air temperature and soil moisture can be identified to determine the right volume of water. The fuzzy system is built based on the chili farming environment and the specifications of the installed water pump. This system uses NodeMCU ESP8266 as the main controller for fuzzy inference calculations. The fuzzy inference calculation process uses the Mamdani method. Information such as air humidity, air temperature, soil moisture and water level will be displayed in real-time on the Blynk application connected to the internet network. The process of watering chili plants in this system is carried out according to a predetermined schedule. Results for seven days showed that the average duration of watering plants was 3.96 seconds with a flow rate ± 43.12 ml/s. By considering the maximum volume of the fuzzy system, the water consumption can be reduced with 30.96% efficiency.